2019
DOI: 10.1002/14651858.cd004039.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma expanders for people with cirrhosis and large ascites treated with abdominal paracentesis

Abstract: Analysis 2.3. Comparison 2 Subgroup analysis of plasma expanders versus no plasma expander regarding modality of paracentesis, Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 139 publications
1
24
0
Order By: Relevance
“…A recent Cochrane review, 34 which included 27 randomised trials, concluded that there was neither any benefit nor any adverse effect in using any plasma expanders, including albumin, polygeline, dextran, hydroxyethyl starch, intravenous infusion of ascitic fluid or crystalloids in patients undergoing paracentesis. The authors further argued that the data on albumin/volume expanders originated from few, small, short‐term trials that are at high risks of systemic errors, selection bias and random errors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review, 34 which included 27 randomised trials, concluded that there was neither any benefit nor any adverse effect in using any plasma expanders, including albumin, polygeline, dextran, hydroxyethyl starch, intravenous infusion of ascitic fluid or crystalloids in patients undergoing paracentesis. The authors further argued that the data on albumin/volume expanders originated from few, small, short‐term trials that are at high risks of systemic errors, selection bias and random errors.…”
Section: Discussionmentioning
confidence: 99%
“…In the only trial comparing albumin to no treatment, there was no difference in mortality ( p = 0.37). There is a systematic review published in 2019 by the Cochrane Hepato‐Biliary Group that was not available for citation during the compilation of current clinical practice guidelines 36 . Based on very low certainty due to the high risk of bias and random errors associated with the small, short‐term trials, the authors could not determine benefit or harm of plasma expansion versus no plasma expansion, or of any differences between plasma expanders.…”
Section: Commentmentioning
confidence: 99%
“…A recent Cochrane review, 52 which included 27 randomized trials, concluded that there was neither any benefit nor any adverse effect in using any plasma expander, including albumin, polygeline, dextrans, hydroxyethyl starch, intravenous infusion of ascitic fluid, and crystalloids in patients undergoing paracentesis. The data on albumin/volume expanders originated from a few, small, short-term trials that were at high risk of systemic errors, selection bias, and random errors.…”
Section: Meta-analysismentioning
confidence: 99%